2021
DOI: 10.1096/fj.202001792r
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule compound berberine as an orally active therapeutic candidate against COVID‐19 and SARS: A computational and mechanistic study

Abstract: The novel coronavirus disease, COVID-19, has grown into a global pandemic and a major public health threat since its breakout in December 2019. To date, no specific therapeutic drug or vaccine for treating COVID-19 and SARS has been FDA approved. Previous studies suggest that berberine, an isoquinoline alkaloid, has shown various biological activities that may help against COVID-19 and SARS, including antiviral, anti-allergy and inflammation, hepatoprotection against drug-and infectioninduced liver injury, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 166 publications
(292 reference statements)
1
43
1
1
Order By: Relevance
“…Our data also show that berberine chloride (BBC) can reduce SARS-CoV-2 replication, similar to what has been found by others [55,56]. BBC was able to block SARS-CoV-2 infectious virus production when added 6 h after the infection was started.…”
Section: Discussionsupporting
confidence: 91%
“…Our data also show that berberine chloride (BBC) can reduce SARS-CoV-2 replication, similar to what has been found by others [55,56]. BBC was able to block SARS-CoV-2 infectious virus production when added 6 h after the infection was started.…”
Section: Discussionsupporting
confidence: 91%
“…Berberine is a substance that shows a broad range of biochemical and pharmacological activities (i.e., anticancer, anti‐inflammatory, antiviral, and antidepressant) and has been proposed for COVID treatment in multiple studies (Varghese et al, 2021 ; Z. Z. Wang et al, 2021 ; Warowicka et al, 2020 ). We did not find any significant correlation for hydroxychloroquine, a highly publicized potential treatment for COVID‐19.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater and sludge samples used in these (and other) surveillance studies have also been leveraged for evaluating the scale and the direct and indirect impacts of outbreaks and associated lockdowns by examining changes in drug consumption, chemical usage, and chemical biomarkers (Choi et al, 2018 ; Lu et al, 2020 ; Reinstadler et al, 2021 ; Senta et al, 2020 ; Varghese et al, 2021 ; Z. Z. Wang et al, 2021 ). In Part 1 of this series, we used both targeted and suspect screening approaches with liquid chromatography—high resolution mass spectrometry (LC‐HRMS) to identify chemicals of interest in primary sewage sludge samples collected over the first 15 weeks of the COVID‐19 pandemic in New Haven, Connecticut, USA, and investigated trends over time during the initial lockdown and reopening phases (Nason et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking and dynamics simulations revealed that BBR significantly interacts with SARS-CoV-2 3CL PRO , S protein, and ACE2 receptor 59 , 60 , 61 ( Table 1 ). This suggests that BBR could prevent viral entry and fusion and interfere with the autophagy processes and the biogenesis of DMV by affecting the 3CL PRO -mediated generation of nsps 4–16.…”
Section: Natural Products Targeting Autophagy To Halt Cell-to-cell Virus Propagationmentioning
confidence: 99%
“…Nonetheless, low bioavailability could be overcome through the inclusion of the natural biomolecules in lipid-based nanoparticles. 61 , 74 Since viruses need to import or synthesize lipid constituents to make DMVs, 62 we theorize that herbal-loaded lipid-nanocarriers, especially those that target nsps involved in the DMV biogenesis and inhibition of the autophagy flux, could be a smart way to easier penetrate cells, modulate autophagy, and hinder SARS-CoV-2. However, since CoVs can create a variety of strategies to use or mimic the host autophagic machinery to replicate, uncovering unexplored autophagy signaling pathways and mechanisms involved in the SARS-CoV-2 infection may open other possibilities for the use of phytocompounds.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%